Engineering electromagnetics [8th ed.] - Hayt, W H; Buck, J A; Akhtar, Jaleel M (Chennai : Mcgrawhill, 2017)
The much awaited revision of Engineering Electromagnetics is finally here. The current edition is now useful for a full-fledged two-semester course on electromagnetics and is as well-suited for the communications engineer as for the electrical engineer. The focus of the adaptation has been on the electrodynamics part and the topics related to transmission lines. The practical aspects of the subject under study have been thoroughly implied in the revision. Inspite of the revision, however, in carrying out the changes, special attention has been paid to retain the original flavor of the text so that the patrons of this well beloved text find it simple to make the transition from 7e to 8e. Salient Features Fundamentals: Classically, the book is known for the in-depth analysis of electrostatics and magnetostatics New chapter on Waveguides and Resonators: In tow with the changing subject requirements, updates in the text are in electrodynamics enabling a better understanding of the applications of electromagnetics in various functional areasPedagogic approach: Since the last edition, there has been an addition of 30+ examples, 7 real-life images, virtual labs etc in line with the student preferencesTable of Content:Vector Analysis Coulomb's Law and Electric Field Intensity Electric Flux Density, Gauss's Law and Divergence Energy and Potential Current and Conductors Dielectrics and Capacitance Poisson's and Laplace's Equations The Steady Magnetic Field Magnetic Forces, Materials and Inductance Time-Varying Fields and Maxwell's Equations Transmission Lines The Uniform Plane Wave Plane Wave Reflection and Dispersion Guided Waves and Radiation Waveguides and Resonators